2014
DOI: 10.1007/s00464-014-3992-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative optical coherence tomography imaging to identify parathyroid glands

Abstract: OCT is capable of distinguishing between parathyroid, thyroid, and adipose tissue. An accurate differentiation between parathyroid tissue and lymph nodes was not possible. The disappointing results compared to the previous ex vivo study are related to problems handling the endoscopic probe intraoperatively. However, further refinement of this new technology may lead to OCT systems with higher resolution and intraoperative probes that are easier to handle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…These results were confirmed by two ex vivo studies from Conti de Freitas et al and our research group . However, in a subsequent in vivo study we were not able to reproduce the excellent results of the ex vivo study . Especially the differentiation between parathyroid glands and lymph nodes was almost impossible.…”
Section: Introductionsupporting
confidence: 66%
“…These results were confirmed by two ex vivo studies from Conti de Freitas et al and our research group . However, in a subsequent in vivo study we were not able to reproduce the excellent results of the ex vivo study . Especially the differentiation between parathyroid glands and lymph nodes was almost impossible.…”
Section: Introductionsupporting
confidence: 66%
“…Given the physical properties of OCT, current literature suggests that this technology could be used for various applications in endocrine head and neck surgeries . However, prior to this study, no other research group described the OCT appearance of neck tissues in both healthy and pathological states.…”
Section: Discussionmentioning
confidence: 99%
“…In otolaryngology, accurate intraoperative tissue identification and differentiation of head and neck tissues is a crucial component of all thyroid and parathyroid surgeries. In an effort to decrease postoperative hypocalcemia, operative time, and increase diagnostic yield, several groups have proposed that OCT could serve as an adjunct tool to identify parathyroid glands during thyroidectomies, confirm the identification of parathyroid adenoma removal in patients with hyperparathyroidism and provide valuable diagnostic information on thyroid nodules . Although OCT appearance of neck tissues have been described in healthy states, no study has yet offered OCT descriptions of thyroid, parathyroid glands, and lymph nodes in pathological states.…”
Section: Introductionmentioning
confidence: 99%
“… is an abstract and published in supplement of journal, not full manuscript). Sensitivity and specificity in distinguishing parathyroid was 84 and 94% , and 69 and 66% by human for ex vivo and in vivo experiments , respectively. The same research group identified parathyroid by measuring the backscattering intensity of their OCT images, the overall rate of correct classifications was 96.15% .…”
Section: Introductionmentioning
confidence: 94%